MEKANISME PENANGGULANGAN PEMBIAYAAN BERMASALAH PADA AKAD MURABAHAH - Mulyono Jamal; Ayu Ruqoyah (Islamic Economics Journal, 2014)
The rise of Islamic economic has established the development of Islamic banking. This indicates that Islamic banking could be competitive with conventional banking. One difference between both banking systems is in lending operation. In conventional bank known as credit, while in Islamic bank known as financing. For certain, financing procedures in Islamic banking refer to Qur’an and Sunnah. Indeed, there are also defaults in its process, because the problems occured after the process. This research aims for knowing the factors which cause the default financing and its mechanism as performed by Bank Muamalat Indonesia (BMI) branch Sragen to solve it. To reach thus aims, the researcher uses field research with deductive explorative methods. The result from this research indicates that there are two factors which cause the default financing, internal factor and external factor. Internal factor is the factor from the customers, while the external factor is the factor from other than customers, ot because of universe. But the most imminent factor at BMI is internal factor, such as the late payment because of neglect. The mechanism runs by BMI branch Sragen is monthly data collection, monitoring and controlling, so that the financing at BMI branch Sragen chategorized as stable.